Research on the Construction and Application of Information Management System Based on Big Data - Liang, Zhe (International Journal of Computer Science and Information Technology, 2024)
This paper focuses on the construction and application of information management systems based on big data in the digital era. It begins by introducing the importance of Information Systems (IS) and big data, and the challenges they face. The paper then provides an overview of big data, including its characteristics, data sources, and common technologies. It also discusses the development and evolution of IS, from the traditional theory-driven approach to the modern data-driven era. The application of big data in is explored, covering data collection, storage, analysis, and visualization. The paper further analyzes the existing data analysis methods, including theoretical analysis, statistical analysis, machine learning, and deep learning. Additionally, it addresses the privacy and security of data, considering legal, ethical, and quality aspects. The application of big data in various industries, such as healthcare, finance, retail, and manufacturing, is also discussed. Finally, the paper looks towards the future, highlighting emerging technologies like AI and quantum computing, and future research directions in big data analysis, security, and integration with AI.